Tumor Location May Independently Predict Survival in Patients With M0 Squamous Cell Carcinoma of the Penis - Li, Kai; Le, Xiang; Wang, Jianqing; Fan, Caibin; Sun, Jian (Frontiers in Oncology, 2022)
Background: To determine the association between tumor location and both clinicopathological characteristics as well as survival of patients with M0 squamous cell carcinoma of the penis (SCCP). Methods: Data of 455 patients diagnosed with M0 SCCP between 1975 and 2018 were collected from the Surveillance, Epidemiology, and End Results (SEER) database of the United States National Cancer Institute. The effects of tumor location on overall survival (OS) and penile carcinoma specific survival (PCSS) were analyzed using the Kaplan-Meier method. The Cox proportional hazards regression model was used to determine the impact of tumor location on PCSS. Results: SCCP was more likely to occur in the prepuce or glans (90%). Although no significant difference was observed between the OS of patients with M0 SCCP in the prepuce or glans and those with M0 SCCP in the body of penis (P= 0.307), the former had better PCSS (P= 0.024). Moreover, M0 SCCP in the prepuce or glans was also significantly associated with better PCSS in patients with advanced age (age≥ 60 years old, P= 0.011), other ethnicities (P= 0.003), T2-T4 stage (P= 0.036), larger tumors (≥ 3cm, P= 0.001), no regional lymph nodes removed (P= 0.044) and radical surgery (P= 0.027). Multivariate analysis confirmed that tumor location is an independent prognostic factor for patients with M0 PCSS [hazard ratio (HR) 1.881, P= 0.026]. Conclusions: Tumor location is an independent prognostic factor for patients with M0 SCCP, and tumors in the prepuce or glans portend better PCSS.